Balanceamento de carteira de renda variável com base na Teoria Moderna do Portfólio - Real, João Paulo Garcez [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The Brazilian population's engagement in investments related to stocks and real estate funds has been growing each year, given the more than 10-fold increase in registered “Cadastro de Pessoa Física” (CPF) on B3 between 2015 and 2022. This study employs the Markowitz optimization model to optimize 11,400 unique portfolios composed of three stocks from different sectors and one real estate fund. The portfolios were determined by combining 20 different stocks, two from each sector, and 10 real estate funds. A total of 10,000 simulations of asset weights were conducted for each portfolio, with a maximum limit of 70% for the weight of any single asset. Asset selection criteria included liquidity, absence of bankruptcy cases, and sector diversification. The historical stock price data used to feed the model spanned from 2015 to 2021. The performance measurement period for the portfolios was the year 2022, and the appreciation or depreciation of the portfolios was calculated, taking into account dividend payments during the period. The results demonstrated that the model effectively mitigated portfolio risk, such that portfolios with higher expected volatility exhibited greater dispersion in portfolio appreciation or depreciation. However, the model did not exhibit the same efficiency in the relationship between expected return and portfolio appreciation. Additionally, through linear regression of the results and dispersion calculation, it was observed that a higher calculated simplified Sharpe ratio for the portfolio corresponded to lower dispersion. Among the top 100 portfolios with the highest calculated index, only three experienced portfolio depreciation.

O interesse da população brasileira por investimentos relacionados à ações e fundos imobiliários cresce a cada ano, dado o aumento de “Cadastro de Pessoa Física” CPFs registrados na B3 de mais de 10 vezes entre 2015 e 2022. O presente estudo utiliza o modelo de otimização de Markowitz para realizar a otimização de 11400 portfólios únicos compostos por três ações de diferentes setores e um fundo imobiliário. Os portfólios foram determinados a partir da combinação de 20 ações diferentes, duas de cada setor e 10 fundos imobiliários e foram realizadas 10000 simulações de pesos dos ativos para cada portfólio, além de limitar a 70% o peso máximo de um ativo. Os ativos foram escolhidos buscando atender critérios de liquidez, ausência de casos de recuperação judicial e divisão de setores. O período histórico de preços das ações utilizado para alimentar o modelo foi de 2015 à 2021. O período utilizado para medir a performance dos portfólios foi do ano de 2022 e foi calculada a valorização ou desvalorização dos portfólios considerando pagamentos de dividendos no período. Os resultados demonstraram que o modelo apresentou eficiência em mitigar o risco dos portfólios, de forma que, portfólios com maior volatilidade esperada apresentaram maior dispersão na valorização ou desvalorização da carteira. O modelo não apresentou a mesma eficiência na relação entre retorno esperado e valorização das carteiras. Também se observou, a partir da regressão linear dos resultados e do cálculo de dispersão que, quanto maior o índice de Sharpe simplificado calculado para a carteira, menor a dispersão e, dentre as 100 carteiras com maior índice calculado, apenas três apresentaram desvalorização do portfólio.
Variable income portfolio balancing based on Modern Portfolio Theory
Keywords: Portfolio management; Renda; Risco; Ações (Finanças); Títulos imobiliários